Ductility of a 60-Story Shearwall Frame-Belt Truss (Virtual Outrigger) Building - Pudjisuryadi P.; Lumantarna B.; Tandya H.; Loka I. (Civil Engineering Dimension, 2012)
Researches have been conducted to study Shearwall-frame combined with belt truss as structural system (SFBT), in which the post-elastic behavior and ductility of this structural system are explored. A 60-story SFBT building, with a ductility set equal to 3.75 (value for fully ductile cantilever wall) is considered. The Elastic Response Spectrum used for design is taken from Zone 2 of Indonesian Seismic Map. Capacity design method according to Indonesian Concrete Code is employed. The seismic performance is analyzed using static non-linear push-over analysis and dynamic non-linear time-history analysis. Spectrum consistent ground motions of the May 18, 1940 El-Centro earthquake N-S components scaled to maximum accelerations of various return periods (50, 200, and 500 years) are used for analysis. The results of this study show that plastic hinges mainly developed in beams above the truss, columns below the truss, and bottom levels of the wall. The building shows no indication of structural instability.